Anaplastic large cell lymphoma mimicking a psoas abscess - Arushi Singh; Piyumi De Silva; Janis Chamberlain; Aniruddh Deshpande (Elsevier, 2020)
We report a case of Anaplastic Large Cell Lymphoma mimicking a psoas abscess in a 6-year-old girl which posed significant diagnostic challenges. She presented with a vague two-month history of anaemia, fevers and back and abdominal pain. Axial imaging including MRI suggested a diffuse, inflammatory lesion in the right psoas muscle and she was commenced on an intravenous antibiotic therapy regimen but with little improvement. An open biopsy was performed and histology confirmed Anaplastic Lymphoma Kinase 1 positive ALCL. To our knowledge, this is only the second case of ALCL with the tissues adjacent the psoas muscle as the primary extra nodal site in the paediatric population. Keywords: Anaplastic large cell lymphoma, Psoas abscess, Paediatric lymphoma